Halogenating and nitrating activity of reagents based on sodium nitrate and alkali metal halides in acetic acid; Russian Journal of Organic Chemistry; Vol. 40, iss. 7 - Filimonov V. D. Viktor Dmitrievich; Kulmanakova Yu. Yu.; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Perederina I. A.; Ki-Whan Chi; Poleshchuk O. Kh. Oleg Khemovich (2004, 2004)
Title screen